The Effect of Workload Analysis and Employee Well-Being Mediated by HRIS System on Nurse Productivity at Kaliwates Hospital Jember - Billardi Atmanagara Fadzliansyah; Budi Santoso; Riyanto Setiawan Suharsono (Universitas KH. Abdul Chalim Mojokerto, 2026)
Kaliwates Jember Hospital as a type C plantation hospital faces challenges in nurse productivity due to high workload and suboptimal employee welfare amid a surge in emergency room patients. This study examines the influence of workload analysis and employee well-being on nurse productivity at Kaliwates Jember Hospital with the HRIS system as an intervening variable. Using an explanatory design quantitative approach with a saturated sample of the entire population of 299 nurses, data was collected through a questionnaire that had been validated and analyzed using Structural Equation Modeling (SEM) based on SmartPLS 4.0. The results showed that workload analysis had a positive effect on nurse productivity through the management of emergency room targets, 12-hour shift efficiency, and physical-mental load mitigation; employee well-being has a positive effect through subjective well-being, workplace, and work-life balance; both affect the HRIS system significantly; HRIS itself increases productivity through automated rotation and real-time analytics. The effect of partial HRIS mediation was confirmed in the moderate category. These findings enrich the theory of Dessler-AMO HR management in the context of Jember type C hospitals, recommending the integration of HRIS workload-well-being modules for the optimization of health human resources